Satisfaction and Revisiting Behaviour of Tourists in India - Raina, Ashish; Rana, Varinder Singh (Nepalese Journal of Hospitality and Tourism Management, 2021)
Despite the fact that the tourists choose and visit the destination after considering the available information, there are certain aspects of the destination which result in the satisfaction of tourists and their revisit behaviour towards a destination. The present paper aims to create a conceptual framework that incorporates the principles of service efficiency system and an efficiency to measure revisiting and recommendation behaviour at various tourist spots in the Union territory of Jammu and Kashmir in India. It used a formal questionnaire to interview 431 visitors to Jammu and Kashmir, India. Primary data was collected and subjected to a statistical software package for analysis. The dimension reduction (factor analysis) technique on the collected data decreased the 25 proposed variables into five new variable constructs. The finding showed that all new variables were relevant for influencing the overall satisfaction level, be them Indians or foreigners. Moreover, the results signified that the total satisfaction leads to the likelihood that families and friends will visit the union territory of Jammu and Kashmir. The data review research can contribute to successful tourism industry policies and strategy preparation.